Innovating biology education: Development a notion as project-based learning e-module in the plant structure and function course to facilitate digital literacy - Sumiati, Ika Dewi; Prasetya, Ferry Budi; Pamungkas, Zakaria Sandy; Amrullah, Jadnika Dwi Rakhmawan; Yusmar, Firdha; Tyas, Intan Lestari Mulyaning; Hsiu-Chen, Liu (Education and Development Research, 2026)
The rapid shift toward digital learning in higher education demands learning resources that not only present content but also facilitate project organization and digital literacy. In response to this need, this study developed a Notion-based e-module integrated with the Project-Based Learning (PjBL) model for the Plant Structure and Function course to support students’ digital literacy. The research employed a Research and Development (R&D) design using the ADDIE model, involving analysis, design, development, implementation, and evaluation stages. Fifty fifth-semester students from the Science Education Program at Universitas Jember participated. Data were collected through expert validation questionnaires, student practicality questionnaires, and pretest–posttest instruments. The product obtained validity scores of 91.875% from material experts and 93.33% from media experts. The practicality score from students reached 90.36%. These findings indicate that the Notion-based PjBL e-module is feasible and practical to support meaningful learning and foster digital literacy. The novelty of this research lies in the integration of a productivity and project-management platform (Notion) as a learning medium in higher education, enabling structured project workflows, collaborative workspaces, and digital documentation for PjBL activities. The developed module offers an alternative digital resource to facilitate technology integration in science education.